إدارة الجودة الشاملة كمدخل لتفعيل أنظمة مراقبة التسيير في المؤسسة - شلابي عطرة (جامعة محمد بوضياف المسيلة, 2015)
The total quality management is one the most important management function in the economicenterprise, When the organisation enter enproves in theirquality programs they willensure the higquality and lowrcost and the organisationobtainsthe ISO certification itmeansthat the enterpriseproducts to meet international standars of quality ,Whichitconsidered a positive factor throughwincustomer trust a ISO the management control is a funactioveryimportant ,itistgrough the use of management control toolsthatcan know the causes of deviation and try to overcomthem and compare themwith real terms Becaus the quality control management system helps to put the correct estimates. The aim of thisstudyisto highlight the overallquality management strategy as a glopal orientation that the enterprisesthroughwhichthem to activat the control management tools,Whichallows for improvedoranizational performance
- دراسة تطبيقية – مؤسسة مطاحن الحضنة بالمسيلة
Keywords: WORDS:Quality ,total quality , ISO , management control.